Sejarah Evolusi Generasi Internet - Saroji, Ahmad; Harmini, Triana; Taqiyuddin, Muhammad (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
This study aims to trace the evolutionary history of the internet across generations, culminating in the fifth generation (5G). Over the last decade, internet technology has undergone rapid development. Each generation of internet technology—1G, 2G, 3 G, 4G, and 5G—comes with its own set of advantages and disadvantages. This article provides an overview of the features and specifications of these internet generations. It examines when Indonesia first adopted internet technology, including identifying the figure known as the